Utilization of plants as food source from Sebaju village forest, Nanga Kebebu village, Nanga Pinoh District, Melawi Regency - Farah Diba; Muhammad Sholihin; Nurhaida Nurhaida (Jurnal Biologi Tropis, 2021)
Forests has a role in supporting food security programs. Sebaju Village Forest, Nanga Kebebu Village, Nanga Pinoh District, Melawi Regency is a village forest area that has the potential of non-timber forest product, one of which is that there are many plants that can be used as food for daily living needs. The research objective was to explore local knowledge of the community and to make an inventory of the types of plants used as food by the communities around the Sebaju village forest, Nanga Kebebu village, Melawi regency, as well ass to describe how to uses and process plants that are used as food by the community. The research method was purposive sampling and data collection was carried out by in-depth interviews with the community in Nanga Kebebu village. The data were analyzed descriptive qualitative in order to obtain a systematic and accurate picture. The results found 58 plant species consisting of 31 families, these plants were dominated by the Anacardiaceae family (8 species). Arecaceae and Moraceae (5 species), Sapindaceae, Phyllanthaceae, Myrtaceae, and Fabaceae (3 species), while one other family each has 1-2 species. The most dominant plant habitats were trees with 40 species (68.96%), 8 types of herbs (13.79%), 4 types of shrubs (6.89%) and the least were lianas and 3 types of shrubs. (5.17%). The part of the plant that was used the most was the fruit, namely 44 species (75.38%), 8 types of leaves (13.79%), while the parts of the plant that were least used were 2 types of tubers (3.45%), 2 types tubers (3.45%), 1 flower (1.72%), 1 seed (1.72%). The largest group of foodstuffs is fruit as much as 40 types (67%), 12 types of vegetables (20%), while the lowest is 3 types of drinks (5%), 3 types of spices (5%), and 2 tubers type (3%). The most widely used food crop processing method is directly used 33 types (56.90%), 10 types of boiled (17.24%), 6 types of sauteed (10.34%) and 5 types of chili sauce (8.62%), Meanwhile, the least used processing methods were 2 types of frying (3.45%) and 2 types of drying (3.45%). Based on their growth status, the highest growth was in the wild, consist of 34 species (59%), and the lowest was cultivated by 24 species (41%) that grew in the Sebaju customary forest area, Nanga Kebebu Village, Nanga Pinoh District, Melawi Regency. Sebaju village forest has high biodiversity as food plant and local knowledge of te community in the use of plants in the forest area makes conservation efforst better because the community strives to be able to make a sustainable management of food from forest.ÃÂ